2012
DOI: 10.1590/s0104-77602012000300012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal treatment on the chemical characteristics of wood from Eucalyptus grandis W. Hill ex Maiden under different atmospheric conditions

Abstract: Thermal treatment (thermal rectification) is a process in which technological properties of wood are modified using thermal energy, the result of which is often value-added wood. Thermally treated wood takes on similar color shades to tropical woods and offers considerable resistance to destructive microorganisms and climate action, in addition to having high dimensional stability and low hygroscopicity. Wood samples of Eucalyptus grandis were subjected to various thermal treatments, as performed in presence (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 3 publications
4
26
0
6
Order By: Relevance
“…The same statistical behavior was reported by Moura et al (2012), for the same treatments and species as in this study. The difference was that they thermally modified wood in laboratory scale, with an oxygen (O 2 ) atmosphere.…”
Section: Insoluble Lignin Contentsupporting
confidence: 85%
See 3 more Smart Citations
“…The same statistical behavior was reported by Moura et al (2012), for the same treatments and species as in this study. The difference was that they thermally modified wood in laboratory scale, with an oxygen (O 2 ) atmosphere.…”
Section: Insoluble Lignin Contentsupporting
confidence: 85%
“…There are few published studies about the chemistry of thermally modified Eucalyptus grandis wood, but we found a very similar Brazilian study where the process was carried out in laboratory scale with a nitrogen (N 2 ) atmosphere (Moura, Brito and Silva Júnior 2012). The authors reported higher averages of holocellulose content for thermally modified 18-year-old (the same age as in this research) Eucalyptus grandis wood than we found, with 58,95 and 54,84% respectively for treatments at 160 and 180 °C.…”
Section: Holocellulose Contentmentioning
confidence: 66%
See 2 more Smart Citations
“…A termorretificação apresenta estudos que indicam sua eficácia na melhora da estabilidade dimensional e do aumento da resistência à degradação biológica e ao intemperismo (Moura et al, 2012). Embora esse processo não esteja consolidado no Brasil, no continente europeu, a madeira termorretificada é largamente empregada na confecção de produtos, como: decks, móveis para jardim, esquadrias, armários internos, parquet, painéis decorativos e interior de saunas (Esteves & Pereira, 2009).…”
Section: Introductionunclassified